The Effects of U.S. Unconventional Monetary Policy on Asia Frontier Developing Economies - Rafiq, Sohrab (IMF Working Papers; Working Paper ;, 2015)
This paper explores the effect of U.S. unconventional monetary policy (QE2) on a group of frontier developing economies (FDEs) in Asia. This paper finds that spillovers emanating from the U.S. on FDEs in Asia have been small. The relative insulation of emerging Asia from the global financial cycle can likely be attributed to the presence of managed capital accounts coupled with shallow financial markets. Should U.S. monetary policy begin to normalize the direct first-round impact on developing Asia is likely to be small.